Heterogeneous multi-layer mobile edge computing for 6G - Pengfei WANG; Boya DI; Lingyang SONG; Zhu HAN (物联网学报)
With the development of the Internet of things,multiple real-time applications will emerge in future 6G communication network.Driven by demands on low-latency services of multiple real-time applications,mobile edge computing (MEC) will become an important technology to improve the user experience and reduce the network cost.However,the computing capacity of a single MEC server is limited,which induces that it is difficult to meet the low-latency requirement of data processing for the computation-intensive applications.A heterogeneous multi-layer mobile edge computing (HetMEC) network architecture was proposed to jointly utilize the computing and transmission resources of both the cloud computing center and multi-layer MEC servers.By reasonably dividing and offloading computing tasks,reliable and efficient computing services were provided for edge applications.Simulation results show that the proposed algorithm could effectively reduce the processing latency,improve the network processing rate and robustness.